A Tin Analogue of Carbenoid: Isolation and Reactivity of a Lithium Bis(imidazolin‐2‐imino)stannylenoid. Issue 24 (21st April 2016) - Ochiai, Tatsumi; Franz, Daniel; Wu, Xiao‐Nan; Irran, Elisabeth; Inoue, Shigeyoshi
Abstract: The lithium bis(imino)stannylenoid (NIPr)2 Sn(Li)Cl (1 ; NIPr=bis(2, 6‐di iso propylphenyl)imidazolin‐2‐imino) was prepared by the reaction of LiNIPr with 0.5 equiv of SnCl2 ⋅diox (diox=1, 4‐dioxane) and the ambiphilic character of the compound was demonstrated by investigations into its reactivity. Treatment of1 with I2 or MeI yielded the oxidative addition products (NIPr)2 SnI2 and (NIPr)2 Sn(Me)I, respectively. In contrast, the reaction of1 with one equivalent of Me3 SiCl resulted in the formation of Me3 SiNIPr and the chlorostannylene dimer [NIPrSnCl]2 . Moreover, the substitution reaction of compound1 with MeLi led to the formation of the methyl‐substituted stannate (NIPr)2 Sn(Li)Me. Abstract : Ambiphilic tin(II) : An elusive bis(imino)stannylenoid, a tin carbenoid analogue, was synthesized by using the highly basic imidazolin‐2‐imino group. Through investigations into the reactivity of the system and computational studies, the ambiphilic character of the stannylenoid was demonstrated.